Pengembangan Kapasitas BUMDES di Desa Bongo III, Kecamatan Wonosari, Kabupaten Boalemo - Machmud, Joice; Imbran, Harijono; Baderan, Umar Sako (Penerbit Goodwood, 2025)
Purpose: This community service program aims to strengthen the management capacity of Village-Owned Enterprises (BUMDes) in Bongo III Village, Wonosari District, Boalemo Regency. The goal is to enhance the community's knowledge, skills, and awareness to manage BUMDes professionally, participatively, and sustainably based on local potential. Methodology/approach: The activity was conducted on April 26–27, 2025, in Bongo III Village using a participatory-experiential workshop method. The program applied adult learning principles and the experiential learning cycle (concrete experience, reflective observation, abstract conceptualization, active experimentation) through interactive discussions, group simulations, and business plan development sessions. Data collection was conducted through field observations and in-depth interviews with village stakeholders. No specific software was used. Results/findings: The training increased participants’ understanding of BUMDes institutional concepts, improved managerial skills, and fostered community awareness regarding the importance of transparent and accountable governance. Participants successfully developed a preliminary business revitalization plan based on local agricultural and fisheries commodities. Conclusion: The training strengthened community capacity to manage BUMDes professionally and encouraged active local economic participation. Limitations: The activity was limited in duration (two days) and did not yet include long-term mentoring or monitoring of BUMDes implementation. Contribution: This study contributes to the field of community development, rural economic empowerment, and public administration by providing a contextual model for institutional capacity building at the village level. It is relevant to academics, practitioners, and policymakers involved in rural governance and economic development.